A Framework for An Integrated E- Government System for Public Service Sectors in Developing Countries Using Design Science Research Methodology - Yolande Rijarua; Jude Osakwe (Universitas Bina Darma, 2023)
This study aimed to develop an integrated framework to enhance government services and improve service delivery for the Namibian government. The Delone and McLean Information Systems success model and the Organizational Information Processing Theory served as the theoretical foundations for this study. The target population consisted of members of the public and a Government Ministry in Namibia. A sample size of 25 participants was selected for the study, utilizing the purposive sampling technique for government employees and the snowball sampling technique for members of the public. Thematic analysis was employed to analyze the data gathered. The study's findings revealed several significant insights. Despite the existence of multiple e-government systems, poor integration among them hindered the ability of the Namibian public service to provide effective and efficient services to citizens. Additionally, the study identified a strong demand from the public for services to be more accessible, convenient, and responsive, including a preference for online applications and faster service delivery. Moreover, the study developed an integrated e-government framework specifically tailored for the Namibian public service, aiming to enhance accessibility, convenience, responsiveness, and cost-effectiveness of services provided to citizens. The implementation of this framework is expected to promote an open and accountable government. It is crucial to emphasize that the successful achievement of e-Government goals relies on factors such as political leadership, support across all government levels, key infrastructure, skilled human resources, a suitable legal and regulatory framework, information resources, and citizen-centric services.